Revitalisasi Bahasa Sangiang Dalam Kegiatan Keagamaan Di Kecamatan Kahayan Tengah Kabupaten Pulang Pisau - Evie Evie; I Komang Widyana; Tardi Edung; I Wayan Sutarwan; Lidya Sinta Bela (Jayapangus Press, 2026)
The Sangiang language is a sacred language within the Kaharingan Hindu religious system, functioning as a medium of spiritual communication in various religious rituals. However, the narrowing of its domain of use, the limited number of speakers, and the weakening of intergenerational transmission have placed the language in a vulnerable condition. This study aims to analyze the forms of maintenance of the Sangiang language, its domains of use, and the roles of actors and institutions in sustaining its continuity in Central Kahayan District, Pulang Pisau Regency. This research employs a descriptive qualitative approach, utilizing observation, in-depth interviews, and documentation involving seven informants. The findings reveal that the maintenance of the Sangiang language occurs primarily through religious ritual practices such as Basarah, Tiwah, and Manyanggar, which serve as its core domains of use. This maintenance is reinforced by the roles of basir and pisor as religious and linguistic authorities, the balai basarah as a space for informal transmission, and the support of religious and educational institutions. However, the process of language transmission remains limited and exclusive, with relatively low participation from younger generations. In addition, modernization and the dominance of the Indonesian language in everyday communication have further restricted the use of the Sangiang language. This study contributes to sociolinguistic scholarship by demonstrating that sacred language maintenance can be sustained through strong ritual domains, even without broader functional expansion. These findings highlight the need for adaptive strategies to ensure the long-term sustainability of religious-based minority languages.